Siderophore profiling of co-habitating soil bacteria by ultra-high resolution mass spectrometry. Issue 1 (14th November 2018) - Boiteau, Rene M.; Fansler, Sarah J.; Farris, Yuliya; Shaw, Jared B.; Koppenaal, David W.; Pasa-Tolic, Ljiljana; Jansson, Janet K.
Abstract : Calcareous soil microbes complete for scarce iron by synthesizing diverse suites of siderophores detectable by ultra-high resolution mass spectrometry. Abstract : The chemical structure of organic molecules profoundly impacts their interactions with metal ions and mineral phases in soils. Understanding the sources and cycling of metal-chelating compounds is therefore essential for predicting the bioavailability and transport of metals throughout terrestrial environments. Here we investigate the molecular speciation of organic molecules that solubilize trace metals in calcareous soils from Eastern Washington. Ultra-high performance Fourier transform ion cyclotron resonance mass spectrometry at 21 Tesla enabled fast and confident detection and identification of metal chelators that are produced by microbes that inhabit these soils based on screening for features that match diagnostic metal isotope patterns. We compared two approaches, one based on direct infusion using the incorporation of a rare isotope to validate true iron-binding features, and another based on separation with liquid chromatography and detection of isotopologues with coherent elution profiles. While the isotopic exchange method requires significantly shorter analysis time, nearly twice as many features were observed with liquid chromatography mass spectrometry (LCMS), mostly due to the reduction in ion suppression where major features limit the sensitivity of minor features. In addition, LCMS enabled the collection of higher quality fragmentation spectra and facilitated feature identification. Siderophores belonging to four major classes were identified, including ferrioxamines, pseudobactins, enterobactins, and arthrobactins. Each of these siderophores likely derives from a unique member of the microbial community, and each possesses different chemical characteristics and uptake pathways, likely contributing to fierce competition for iron within these soils. Our results provide insight into the metabolic pathways by which microbes that co-inhabit calcareous soils compete for this essential micronutrient.